Los renos de Amadjuak - Jarich Oosten; Frédéric Laugrand (Recherches amérindiennes au Québec, 2016)
This paper describes and analyses the introduction of reindeer herding in Amadjuak, on Baffin Island, in 1921. The operation involved several Saami families and Inuit, hired at the last moment to help the Saami and take over reindeer herding. But the operation resulted in a failure and all the reindeer died, many of them eaten by wolves and dogs. Using archival sources – and more particularly the journal of the Hudson’s Bay Company agent – as well as oral sources, the authors evoke the reasons explaining this dramatic experience. They emphasize the difficulty of transforming hunters into herders, these two activities being connected with quite different perspectives of the relationships between human beings and animals. Finally they stress the fact that among Inuit, the caribou is often associated with the deceased and with spirits (ijirait), a connection that is never made with respect to the reindeer imported by the qallunaat. Cet article décrit et reconstruit l’introduction de l’élevage de rennes à Amadjuak, en Terre de Baffin, en 1921. L’opération a mobilisé plusieurs familles de Saamis, ainsi que des Inuits recrutés au dernier moment pour aider ces familles et prendre la relève au départ de ces dernières. Elle se solde cependant par un cuisant échec, les derniers rennes étant finalement mangés par les loups et par les chiens. À partir de sources écrites – en particulier le journal du poste de la Hudson’s Bay Company – et de sources orales, les auteurs évoquent les raisons de cette issue dramatique et s’arrêtent plus particulièrement sur la difficulté de transformer des chasseurs en éleveurs, la chasse et l’élevage relevant de schèmes contrastés. Ils soulignent finalement que, pour les Inuits, le caribou demeure aussi associé aux esprits ijirait et aux défunts, une connexion qui ne s’applique jamais aux rennes importés par les Qallunaats. Este artículo describe y reconstruye la introducción de la cría de renos en Amadjuak en Tierra de Baffin en 1921. La operación movilizó a varias familias Saami e Inuit, ...